DAKWAH ISLAM DI ERA DIGITAL: PERSPEKTIF SOSIAL DAN BUDAYA - Nurul Hikmatur romdoni; May Putri Wulandari (Program Studi Komunikasi dan Penyiaran Islam, 2025)
Digital technology transformation has significantly impacted Islamic propagation (dakwah), particularly within Indonesia's multicultural society. Digital media platforms such as YouTube, Instagram, and TikTok have become primary tools for delivering religious messages, replacing conventional methods. This study aims to explore the utilization of digital media in Islamic propagation and identify the arising social and cultural implications. Employing a qualitative approach based on library research, this study analyzes literature related to digital communication theories and social transformation. The findings reveal that digital media facilitates access to and dissemination of Islamic teachings, enhances inclusivity, and fosters virtual communities that promote spiritual solidarity. However, challenges such as message distortion, low digital literacy, and the risk of disseminating unreliable information also arise. The study concludes that the success of digital Islamic propagation depends on innovative, relevant, and socially adaptive strategies.